2019
DOI: 10.1002/jbmr.3903
|View full text |Cite
|
Sign up to set email alerts
|

Nonremission and Recurrent Tumor-Induced Osteomalacia: A Retrospective Study

Abstract: Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic syndrome. It is curable by excision of the causative tumor. However, a few cases may persist or relapse after tumor resection. We aimed to investigate the rate of these events and related factors. We retrospectively studied TIO patients treated with surgery in a tertiary hospital. TIO was established based on a pathologic examination or the reversion of hypophosphatemia. Refractory TIO patients consisted of those with nonremission or recurrent hypophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 19 publications
1
41
2
5
Order By: Relevance
“…(1,2) The largest cohort from a single center included 230 patients. (3) FGF23 excess leads to hypophosphatemia due to renal phosphate wasting and inappropriately normal or low 1.25 dihydroxy vitamin D. As a result, patients often present with a long history of musculoskeletal pain, fatigue, proximal muscle weakness, gait disturbance and multiple fractures. These debilitating symptoms are a consequence of severe hypophosphatemia and can lead to long-term disability and considerable morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,2) The largest cohort from a single center included 230 patients. (3) FGF23 excess leads to hypophosphatemia due to renal phosphate wasting and inappropriately normal or low 1.25 dihydroxy vitamin D. As a result, patients often present with a long history of musculoskeletal pain, fatigue, proximal muscle weakness, gait disturbance and multiple fractures. These debilitating symptoms are a consequence of severe hypophosphatemia and can lead to long-term disability and considerable morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Although complete tumor resection results in resolution of symptoms in most patients, (3) the diagnosis of TIO is commonly delayed due to its rarity and unspecific symptoms, and because tumor localization remains a challenging task. (4) In clinical practice TIO is largely known as a chronic condition that causes muscle quality deterioration and has a significant impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…After the tumor has been localized, complete tumor resection with wide margins is recommended to decrease the likelihood of persistent or recurrent disease (Table 3). In a retrospective review of 230 patients with TIO, Li et al reported the incidence of persistent and recurrent TIO after the first surgery to be 11.3 and 7.0%, respectively, with the majority of cases due to suboptimal tumor resection [24]. In multivariable analysis, female sex, spine tumors, and bone tissue-involved tumors were identified as factors associated with refractory outcomes [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 230 patients with TIO, Li et al reported the incidence of persistent and recurrent TIO after the first surgery to be 11.3 and 7.0%, respectively, with the majority of cases due to suboptimal tumor resection [24]. In multivariable analysis, female sex, spine tumors, and bone tissue-involved tumors were identified as factors associated with refractory outcomes [24]. Additionally, each 0.31 mg/dL increase in the preoperative serum phosphorus level (range 0.59 to 2.1 mg/dL) was found to reduce the risk of refractoriness by more than 40% [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation